A Multi-Enzymatic Cascade Reaction for the Stereoselective Production of γ-Oxyfunctionalyzed Amino Acids - Enoki, Junichi; Meisborn, Jaqueline; Müller, Ann-Christin; Kourist, Robert (Frontiers in Microbiology, 2016)
A stereoselective three-enzyme cascade for synthesis of diasteromerically pure γ-oxyfunctionalized α-amino acids was developed. By coupling a dynamic kinetic resolution using an N-acylamino acid racemase and an L-selective aminoacylase from Geobacillus thermoglucosidasius with a stereoselective isoleucine dioxygenase from Bacillus thuringiensis, diastereomerically pure oxidized amino acids were produced from racemic N-acetylamino acids. The three enzymes differ in their optimal temperature and pH-spectra. Their different metal cofactor dependencies lead to inhibitory effects. Under optimized conditions, racemic N-acetylmethionine was quantitatively converted into L-methionine-(S)-sulfoxide with 97% conversion and 95% de. The combination of these three different biocatalysts allows the direct synthesis of diastereopure oxyfunctionalized amino acids from inexpensive racemic starting material.